High resolution ultrasonography and magnetic resonance imaging in the evaluation of tendino-ligamentous injuries around ankle joint - Nevien El-Liethy; Heba Kamal (The Egyptian Journal of Radiology and Nuclear Medicine, 2016)
Purpose: The aim of this study was to rule out the diagnostic accuracy of both ultrasonography (US) and magnetic resonance imaging (MRI) for the assessment of tendino-ligamentous pain around the ankle joint. Patients and methods: This study included 35 patients (25 females and 10 males) complaining of unilateral ankle pain (acute or chronic), and they were subjected to plain X-ray (to exclude osseous pathology), US and MRI examinations. Results: The study included 35 patients where 20 patients showed tendon pathology that was diagnosed into 21 pathological entities by both US and MRI imaging modalities with no difference in interpretation between them. 21 patients had pathological ligaments which were diagnosed by both ultrasound and MRI. However, two ligamentous lesions were diagnosed as partial tear by US, while MRI diagnosed them as complete tear. Associated findings were also diagnosed as retrocalcaneal bursitis in two patients, joint effusion in four patients and joint synovitis in three patients. Conclusion: US is an excellent tool for imaging soft tissue abnormalities, as it allows rapid, in-expensive detailed examination of the structures of the ankle joint. US and MRI are two complementary tools of investigation with the former being used as primary effective tool of investigation and the latter is done to confirm the diagnosis.